ABCC Subfamily Vacuolar Transporters are Involved in Pb (Lead) Detoxification in Saccharomyces cerevisiae - Sousa, Cátia A. (2016)
The present work has as objective to contribute for the elucidation of the mechanism associated with Pb detoxification, using the yeast Saccharomyces cerevisiae as a model organism. The deletion of GTT1 or GTT2 genes, coding for functional glutathione transferases (GST) enzymes in S. cerevisiae, caused an increased susceptibility to high Pb concentrations (500-1000 μmol L(-1)). These results suggest that the formation of glutathione-Pb conjugate (GS-Pb), dependent of GSTs, is important in Pb detoxification. The involvement of ATP-binding cassette (ABC) vacuolar transporters, belonging to class C subfamily (ABCC) in vacuolar compartmentalization of Pb, was evaluated. For this purpose, mutant strains disrupted in YCF1, VMR1, YBT1 or BPT 1 genes were used. All mutants tested, without vacuolar ABCC transporters, presented an increased sensitivity to 500-1000 μmol L(-1) Pb comparative to wild-type strain. Taken together, the obtained results suggest that Pb detoxification, by vacuolar compartmentalization, can occur as a result of the concerted action of GSTs and vacuolar ABCC transporters. Pb is conjugated with glutathione, catalysed by glutathione transferases and followed to the transport of GS-Pb conjugate to the vacuole by ABCC transporters.